Structure–Property Correlation of Infill Topology and Density on Tensile and Flexural Performance of FDM-Printed PLA and ABS - Omprakash Sahu; Chinmay Saraf; Shaheen Beg Mughal (International Journal of Fracture Mechanics and Damage Science, 2026)
Additive Manufacturing (AM), particularly Fused Deposition Modeling (FDM), has become a widely adopted manufacturing technology due to its design flexibility, low cost, and capability for rapid prototyping. However, the mechanical performance of FDM-printed components is strongly influenced by internal structural parameters such as infill pattern and infill density, in addition to the intrinsic material behaviour. This study investigates the structure–property relationship between infill topology, density, and mechanical performance of PLA and ABS thermoplastics fabricated using FDM technology. A full factorial experimental design (2 × 4 × 3) was implemented to systematically evaluate the effects of material type (PLA, ABS), infill pattern (Grid, Triangles, Honeycomb, Gyroid), and infill density (20%, 50%, 80%) on tensile and flexural behaviour. A total of 240 mechanical tests were conducted following ASTM D638 and ASTM D790 standards. Statistical analysis using two-way ANOVA confirmed that infill density is the dominant factor affecting mechanical performance, accounting for more than 90% of strength variation, while infill pattern and pattern–density interactions also exhibit significant effects. Results indicate that the Triangles pattern provides the highest tensile strength and reliability, whereas the Honeycomb structure offers superior flexural performance due to its efficient shear load distribution. The Gyroid pattern demonstrates improved ductility and energy absorption, making it suitable for impact-resistant applications. To incorporate structural reliability, Weibull fracture statistics were integrated with ANOVA results, and an Integrated Mechanical–Reliability Index (IMRI) was proposed for combined strength–reliability assessment. The findings demonstrate that optimal infill design must consider both deterministic strength and probabilistic reliability. This integrated approach provides a reliability-driven framework for structural optimization of FDM components, enabling more informed design decisions for functional additive manufacturing applications
Keywords: ABS; ANOVA; Additive manufacturing; Flexural strength; Fused Deposition Modeling (FDM); Infill density; Infill pattern; PLA; internal lattice structures; mechanical reliability; tensile strength; weibull analysis